Ethical Efficacy as a Measure of Training Effectiveness: An Application of the Graphic Novel Case Method Versus Traditional Written Case Study - Fischbach, Sarah (Journal of business ethics, 2015)
The study explores the use of Graphic Novels as an innovative form of training that may improve an individual’s ethical efficacy. A quantitative comparison of the graphic novel method and the traditional written case study is analyzed. The literature on ethics, graphic novels, and training are brought together from theories of narrative and literature perspective to formulate a study. The study uses a 2 × 2 repeated-measure MANOVA to analyze the participant’s reaction to bribery situations based on varying levels of ‘grayness.’ The overall study finds that ethical efficacy increases with the use of the graphic novel method. The greatest improvements are in the individual’s level of self-efficacy and understanding of principle-based ethical issues. In addition, the participant’s level of industry experience may play a factor in applying the graphic novel technique. Finally, guidelines on how to effectively utilize the graphic novel method are stated. Improving ethical efficacy through business ethics training may help improve an individual’s self-efficacy, involvement and principle-based understanding. The study explores the use of Graphic Novels as an innovative form of training that may improve an individual’s ethical efficacy. A quantitative comparison of the graphic novel method and the traditional written case study are analyzed. Literature on ethics, graphic novels, and training are brought together with theories of narrative and literature perspective to formulate a study. The study uses a 2 × 2 repeated-measure MANOVA to analyze the participant’s reaction to bribery ethical situations based on varying levels of ‘grayness.’ The overall study finds that ethical efficacy increases with the use of the graphic novel method. The greatest improvements are in the individual’s level of self-efficacy and understanding of principle-based ethical issues. In addition, the participant’s level of industry experience may play a factor in applying the graphic novel technique. Finally, guidelines on how to effectively utilize the graphic novel method is set forth.